2020
DOI: 10.1039/d0sc04655h
|View full text |Cite
|
Sign up to set email alerts
|

f-Element silicon and heavy tetrel chemistry

Abstract: The last three decades have seen a significant increase in the number of reports of f-element carbon chemistry, whilst the f-element chemistry of silicon, germanium, tin, and lead remain underdeveloped...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 94 publications
4
32
0
Order By: Relevance
“…The Sm–Si distances of 3.0891(11) and 3.0987(10) Å clearly show the oxidation state of Sm as Si–Sm(II) bonds are typically found between 3.15 and 3.23 Å. 18 Of all reported Si–Sm(III) complexes, only [{K(18-crown-6)} 2 Cp][Cp 3 Sm{Si(SiMe 3 ) 3 }] (3.1013(17) Å) 17 exhibited a bond longer than those in 2Sm . The DME adduct of SmCl 3 [SmCl 3 ·(DME) 2 ] is monomeric, 41 and its Si–Cl distances (2.647(1)–2.656(1) Å) are only barely longer than those of 2Sm (2.649(1)/2.6390(9) Å).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The Sm–Si distances of 3.0891(11) and 3.0987(10) Å clearly show the oxidation state of Sm as Si–Sm(II) bonds are typically found between 3.15 and 3.23 Å. 18 Of all reported Si–Sm(III) complexes, only [{K(18-crown-6)} 2 Cp][Cp 3 Sm{Si(SiMe 3 ) 3 }] (3.1013(17) Å) 17 exhibited a bond longer than those in 2Sm . The DME adduct of SmCl 3 [SmCl 3 ·(DME) 2 ] is monomeric, 41 and its Si–Cl distances (2.647(1)–2.656(1) Å) are only barely longer than those of 2Sm (2.649(1)/2.6390(9) Å).…”
Section: Resultsmentioning
confidence: 91%
“…A recent review by Réant, Liddle, and Mills, which does an excellent job describing the development of the field, listed 54 structurally characterized examples with RE–silicon bonds, 18 suggesting that RE silyl chemistry has reached a degree of maturity. The number of 54 examples is still not very high, given that there are 17 RE elements.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, they can be efficiently synthesized from the corresponding divalent or trivalent rare-earth halides and alkali metal silylamides in high yields and show good solubility in aliphatic solvents. , In the case of the solvent-free three-coordinate [Ln­{N­(SiMe 3 ) 2 } 3 ], despite the steric congestion of the silylamides around the trivalent metal center, several Lewis base adducts have been isolated. In compounds of the type [Ln­{N­(SiHMe 2 ) 2 } 3 (thf) 2 ] ( Anwander amide ) bearing sterically less demanding bis­(dimethyl­silyl)­amide groups, the thf coligands can be displaced by different monodentate or bidentate chelating donors. , As an example, the group of Anwander has shown that the two coordinated thf molecules in [Y­{N­(SiHMe 2 ) 2 } 3 (thf) 2 ] can be substituted by one or two carbene donor ligands to form [Y­{N­(SiHMe 2 ) 2 } 3 (NHC)] or [Y­{N­(SiHMe 2 ) 2 } 3 (NHC) 2 ] (NHC = 1,3-dimethyl­imidazolin-2-ylidene) . Among others, silylenes are known as strong σ-donor ligands frequently used in transition metal chemistry. In the continuation of our previous studies on the synthesis of compounds bearing rare Ln–Si­(II) bonds, , we have examined in this work the reaction between a series of divalent and trivalent rare-earth metal silylamide precursors with two different types of silylene ligands. We used the bis­(silylene) LSiFcSiL (L = PhC­(N t Bu) 2 , Fc = ferrocenediyl) and the pyridine-functionalized silylene L N Si (N = 2-(methylamido)­pyridine) owing to their chelating abilities.…”
Section: Introductionmentioning
confidence: 99%
“…28 Among others, silylenes are known as strong σdonor ligands frequently used in transition metal chemistry. 30−34 In the continuation of our previous studies 12 on the synthesis of compounds bearing rare Ln−Si(II) bonds, [9][10][11]35 we have examined in this work the reaction between a series of divalent and trivalent rare-earth metal silylamide precursors with two different types of silylene ligands. We used the bis(silylene) LSiFcSiL 36 were especially interested to investigate whether the unusual reduction-induced bond cleavage reactivity that occurs when using the diaminopyridine-based LSiN′SiL (N′ = 2,6-di-(ethylamido)pyridine) bis(silylene) ligand (Scheme 1) would also be observed with the related bis(silylene) LSiFcSiL and mono(silylene) L N Si ligand frameworks. ]…”
Section: ■ Introductionmentioning
confidence: 99%
“…All relevant existing complexes were surveyed in a recent review. 32 We report here on the synthesis, structural determination and multi-nuclear high-resolution NMR characterisation of two new ytterbium(II) tetryls, [Yb{Ge(SiMe3)3}2. (thf)3] (Yb-Ge) and its heavier analogue [Yb{Sn(SiMe3)3}2.…”
Section: Introductionmentioning
confidence: 99%